Desarrollo de una plataforma empresarial para dar soporte a los procesos de administración de la conexión a INTERNET, administración de usuarios, administración de facturas, gestión de banners publicitarios, administración de carga y descarga de archivos desde el servidor y gestión de contenidos del Portal WEB, para la Empresa proveedora de INTERNET "NECUSOFT" de la ciudad de Loja. - Dávila Tinizaray, Diego Fernando (2010)
The present project initiates in the month of June of the 2009 for the sake of selling off an Entrepreneurial Platform to support connection administration's processes to internet, administration of users, administration of invoices, step of publicity banners, carrying administration and archival unloading for the company Nettplus of the city of Loja so that the above mentioned processes enforce themselves of an efficient and efficacious way. The collecting process of requests and of the whole information required for the stage of analysis has come true on the basis of investigating techniques as opinion polls and interviews addressed to the executives, employees, and a significant sample of the company customers. The information has been analyzed and organized with the focus supplied by the methods inductive deductive and scientific, which allowed obtaining high quality information as well as the functional requests and no functional of the platform. In order to initiate the process of designing development of the platform, a comparison comes true enter the existing methodologies of development, of the ones that the methodology of development of software used is ICONIX between, that UML is a flexible, iterative and incremental methodology that makes use of the tool for to model the interaction of the system, generating the pertinent documentation to obtain an efficient platform, chord with the business necessity. The entrepreneurial platform for the company Nettplus has been designed with an architecture customer servant, and the model boss sight controlling adequate for a surroundings web. For the developmental stage of the platform an analysis to elect from among the available technologies for development of applications web at present came true, and it is decided unilaterally to work with the platform Java Enterprise 5, and the technologies based in her, proposals the division Jboss of Red Hat, in view of robustness, stability, portability and perfect integration constitute the perfect option for the suchlike development of platforms